PI3K/AKT signaling in cancer - Rosen, Neal (Henry Stewart Talks, 2011)
PI3K/AKT signal transduction pathway, Tumors with frequent dysregulation of PI3K signalling, Modalities for inhibiting PI3K-AKT signaling currently in development, AKT1/2 inhibitor (Merck), PI3K/AKT in breast cancer, AKTi-1/2 inhibits AKT signaling and causes G1 arrest, The Herceptin-resistant, Effect of AKT inhibition on glucose levels, Mutated elements in mitogenic signaling pathways in tumors, Coexistent K-Ras or B-Raf mutation, Genes encoding several components of mitogenic signaling pathways are mutationally activated in tumors, Integrators of multiple signaling pathways (OR-gates), The effects of combined inhibition of AKT and MAPK on the phosphorylation of translational regulatory proteins, Knockdown of 4EBP1 expression, Feedback inhibition of insulin/IGF-1 signaling, The concept of feedback, Clinical effects of Rapamycin-like drugs, mTORC1 vs. AKT regulated feedback, Clinical uses of AKT inhibitors